Salicylic Acid Alleviates Aluminum Toxicity in Soybean Roots through Modulation of Reactive Oxygen Species Metabolism - Liu, Ning; Song, Fengbin; Zhu, Xiancan; You, Jiangfeng; Yang, Zhenming; Li, Xiangnan (Frontiers in Chemistry, 2017)
As an important signal molecule, salicylic acid (SA) improves plant tolerance to aluminum (Al) stress. The objective of this study was to investigate the effects of exogenous SA application on the dynamics of endogenous SA and reactive oxygen species in soybean (Glycine max L.) exposed to Al stress. The roots of soybean seedlings were exposed to a combination of AlCl3 (30 μM) and SA (10 μM)/PAC (100 μM, paclobutrazol, SA biosynthesis inhibitor) for 3, 6, 9 and 12 h. Al stress induced an increase in endogenous SA concentration in a time-dependent manner, also verified by the up-regulated expression of GmNPR1, an SA-responsive gene. Al stress increased the activities of phenylalanine ammonia-lyase (PAL) and benzoic acid 2-hydroxylase (BA2H), and the contents of SA, O2- and malondialdehyde (MDA) in the root apex. The application of exogenous SA increased PAL and BA2H, and reduced O2- and MDA contents in soybean roots under Al stress. PAC inhibited the SA induced increase in BA2H activity. In addition, the SA application resulted in a rapid increase in hydrogen peroxide (H2O2) concentration under Al stress, followed by a sharp decrease. Compared with the plants exposed to Al alone, Al+SA plants possessed higher activities of superoxide dismutase, peroxidase and ascorbate peroxidase, and lower catalase activity, indicating that SA alleviated Al-induced oxidative damage. These results suggested that PAL and BA2H were involved in Al-induced SA production and showed that SA alleviated the adverse effects of Al toxicity by modulating the cellular H2O2 level and the antioxidant enzyme activities in the soybean root apex.